Odpowiedzialność zawodowa, a wprowadzanie uczniów klas IV szkoły podstawowej w świat historii. Oczekiwania społeczne, a codzienna rzeczywistość – wyniki obserwacji młodego nauczyciela - Hurysz , Mateusz (Studia Edukacyjne, 2017)
The teacher today works in close relationship with others, which forces him to accept a limited set of attitudes and ways of action. I assume for the purposes of this paper two groups of factors for the teacher modeling approach: external – pedagogical supervision and school-imposed regulations deriving from state teachers’ and society’s expectations, especially from parents and students themselves, the internal factors – the process of educating and teaching every teacher and crucial, long-term formation of conscience. Based on this specific quadrangle I will present the first stage of introducing a young man to the world of history at the second stage of compulsory education in Polish schools. The assumption is that a primary school teacher may encourage or discourage the student to continue learning history, both national and global, in the middle school or in the secondary school. This is a great responsibility, which even teachers themselves often forget. The article indicates how all of this corresponds to social expectations and what everyday reality for a young teacher is...